From Competition to Market Diversification and Business Sales Growth: Insights from Nigeria - OLUBIYI, Timilehin Olasoji; ITAI, Muktar, M.; KOWO, Solomon Akpoviroro; ODUMESI, Abolaji Oladimeji (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This research examines the impact of diversification capability on the growth of selected consumer goods companies, offering insights from Sub-Saharan Africa. The study employed a survey design, focusing on a population of 22,466 individuals, a sample size of 491 respondents was determined using the Research Advisor Table, Data was collected via a questionnaire, yielding a response rate of 97.76%, and analysed using descriptive and inferential statistics, including regression analysis. The results revealed that diversification capability positively influenced business growth, with innovation capacity having a significant and positive impact on profitability (β = 0.842, t = 29.782, p<0.05). The ability to diversify was found to positively affect business sales growth. The study is limited to consumer goods companies listed in Nigeria, and the findings may not generalise to other industries or regions. Future research could explore the impact of diversification capability in other sectors or African countries. The study suggests that companies in the consumer goods sector should develop diversification capabilities to gain a competitive edge and enhance their sustainable competitive advantage. The novel insights provide valuable on how diversification capability contributes to business growth in the consumer goods sector, particularly in a developing economy like Nigeria, highlighting the strategic importance of diversification in achieving profitability and market growth.